Relevansi Pendidikan Akhlak di Masa Modern Perspektif Bediuzzaman Said Nursi - Setiawan, Agus (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2016)
Said Nursi said that in moral education is based on his understanding of the Qur'an and the inspiration of Allah SWT. The main task of moral education is to strengthen the principles possessed by humans to achieve human levels such as harmonious and balanced prophet in a positive way that gave birth to a noble attitude with morality karimah. There are 9 principles relating to morals contained from some books by Said Nursi, namely strengthening the faith, clinging to the Qur'an, the importance of understanding the essence of human creation, the importance of understanding the universe, the importance of understanding the 'al-Husna asthma, the importance of knowing Signs of doomsday, the importance of believing the end of the world, imitating the prophet Muhammad, and inculcating sincere, piety and alms. And from some of the principles / morals above, the most fundamental thing in strengthening his understanding is his interpretation of God, man, and the universe. First morality to God is related to the principle of strengthening the faith. Said Nursi believes that the ultimate faith in living a life. The faith in question is faith that is sufficient in the faith. Second is morality to man, is a manifestation of understanding the real creation of man. Humans have a tendency to goodness and always to the right path. And thirdly, the morals to the universe, Said Nursi says that the universe with all its elements, from the largest to the smallest, from inanimate to living things, are all created with a dose corresponding to their respective portions. Perspective Said Nursi about moral education, of course, very relevant to the context of character education as proclaimed by the government at this time. Theoretically Said Nursi's thought is based on al-Qur'an as-Sunnah and in practice can provide spiritual values through reason and morals so it is expected to change society to be morally in everyday life, both at school and at home.